Land Conservation Program Paddy Fields - Hamdi Sari Maryoni (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
This study discusses the conversion of paddy fields in the village Sekarsuli Berbah District of Sleman which continued to increase from time to waktu. Kabupaten Sleman establish areas of productive agricultural centers to maintain the ability to produce food, especially rice. For research purposes; (1) identify the value of land and land development rights value fields and, (2) identify the response of farmers to estimate the value of land development rights if it is offered as a basis for determining the value of conservation programs. Subjects were farmers in the Sekarsuli as many as 35 people using primary sampling. Data snowball of observations using instruments terbuka. Data questionnaire secondary use of data from BPS. Paddy land conservation programs will be sustained when the value of the program is received and in accordance with the expectations of land owners. One model for determining the conservation program is the value of land development rights. The value of land development rights is the difference between the expected value of optimal land to the value of land. Estimated value of the subsequent land development rights offered to landowners if they agreed that if the value was used as the basis of determining the value of land conservation programs. Response data analysis techniques landowners using logit regression. The estimation results concluded (1) obtained an average value of land use by 55% of the estimated value of optimal land. The amount of excess is an average of 45%, referred to as the value of land development rights (Value Development Right). (2) Respondents agree with the conservation program as many as 24 respondents, disagree as much as 11 responden.Luas land and public facilities Distance lands to be an influential factor on the farmer's decision to accept or reject the offered programs. Keywords: conservation of paddy fields, and the value of land